Information Literacy Programme at the University of Namibia (Journal for Studies in Humanities and Social Sciences, 2019)
The research was done to investigate the information seeking behaviour among students at the University of Namibia. The study was conducted to fi nd out the reasons why students do not attend the information literacy training off ered by the University of Namibia library and to recommend ways in which information literacy can be integrated into the curriculum. The study used both quantitative and qualitative data collection methods by employing self-administered questionnaires distributed to participants and using focus group interviews with library staff to ensure validity of the results. The fi ndings showed varied reasons for low turnout by the students for training and chief among these are poor communication of information to students concerning the days of training and lack of information on the part of students concerning the signifi cance of training in information literacy. The fi ndings also revealed that many students had the competence to use the internet, although they lacked knowledge of particular websites and databases which were relevant to their studies. The majority of students suggested more training as measures that can be taken to improve information literacy at the university and pointed out that students must be informed properly about training sessions. It was observed that the training did not have a written curriculum and it was recommended that a curriculum be developed to meet the needs of diff erent students. It was also recommended that critical databases must be made available to students through distribution of pamphlets and wall posters so that those students who are capable of using computers can access these databases that are critical to their studies.